Dari Surat ke Chat: Evolusi Komunikasi Manusia pada Zaman Gen Z - Yunita, Dewi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The development of information and communication technology has transformed the way humans interact from a manual era based on physical writing such as letters to a digital era based on instant chat. This transition is very obvious in Generation Z (born around 1997-2012), who grew up with the development of the internet, smartphones, and instant messaging applications. This communication evolution does not only shift the message medium, but also influences language structure, social dynamics, relational patterns, and cultural norms of interaction. This article uses a literature review method to analyze the evolution of human communication from traditional letters to digital chat in the context of Gen Z, by examining the latest academic literature from 2020 to 2025. The results of the study show that the change in medium brings consequences for linguistic changes, communication pragmatics, and psychosocial patterns that are unique to Gen Z. On the other hand, the tendency of digital communication also brings challenges such as social friction due to digital multitasking, the risk of misinformation, and the need for stronger media literacy. These findings indicate that the evolution of communication in Gen Z is a multidimensional phenomenon that requires interdisciplinary understanding to comprehensively explain its implications for society.